2022
DOI: 10.1007/s10834-022-09818-3
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Economic Well-Being in Sole and Joint Physical Custody Families

Abstract: Previous research has repeatedly shown that separation or divorce can lead to a substantial decline in economic resources, and that it is mostly mothers who suffer from the severe economic consequences. Because it has also been established that the post-separation care arrangement that a family practices is a central factor in explaining mothers’ poor economic situations after family dissolution, this study investigated the association between physical custody arrangements (sole physical custody, asymmetric jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Given that separation and divorce have been linked to a decline in economic well-being (Mortelmans, 2020) and social contact (Kalmijn & van Groenou, 2005), practicing JPC should also improve the well-being of resident parents because sharing physical custody equally or almost equally with the other parent allows for more time to invest in other life domains, such as paid employment, leisure activities, and personal relationships. In line with these assumptions, studies have demonstrated that for mothers, practicing JPC was associated with fewer problems in combining paid employment and child care (Bakker & Karsten, 2013), a greater probability of being employed (Bonnet et al, 2018), and higher self-assessed economic well-being (Augustijn, 2023). Furthermore, research demonstrated that JPC was positively linked to mothers' chances of repartnering (Schnor et al, 2017) as well as their participation in personal leisure activities outside the home-even though post-separation care arrangements were not related to the social life of fathers (Botterman et al, 2015).…”
Section: Joint Physical Custody and Resident Parents' Well-beingmentioning
confidence: 93%
“…Given that separation and divorce have been linked to a decline in economic well-being (Mortelmans, 2020) and social contact (Kalmijn & van Groenou, 2005), practicing JPC should also improve the well-being of resident parents because sharing physical custody equally or almost equally with the other parent allows for more time to invest in other life domains, such as paid employment, leisure activities, and personal relationships. In line with these assumptions, studies have demonstrated that for mothers, practicing JPC was associated with fewer problems in combining paid employment and child care (Bakker & Karsten, 2013), a greater probability of being employed (Bonnet et al, 2018), and higher self-assessed economic well-being (Augustijn, 2023). Furthermore, research demonstrated that JPC was positively linked to mothers' chances of repartnering (Schnor et al, 2017) as well as their participation in personal leisure activities outside the home-even though post-separation care arrangements were not related to the social life of fathers (Botterman et al, 2015).…”
Section: Joint Physical Custody and Resident Parents' Well-beingmentioning
confidence: 93%
“…Studies based on German data come to different conclusions on the permanence of income losses after separation, depending on the data and sample. Augustijn (2022) investigates the association between separated mothers' subjective evaluations of economic well-being and the physical custody arrangement, based on a sample drawn from the 2019 Family Models in Germany (FAMOD) study. The researcher concludes that mothers in joint custody settings fare better than their peers with sole custody.…”
Section: Background and Hypothesesmentioning
confidence: 99%